The Necessity of a Strategic Approach to Romanian Tourism - Smaranda Toma; Daniela Mihai (Ovidius University Annals: Economic Sciences Series, 2022)
This paper presents a SWOT analysis of the tourism destination Romania, to take advantage of opportunities and transform strengths into competitive advantages, eliminate or improve weaknesses, reduce threats, and establish a defensive plan to eliminate weaknesses and overcome threats. Although it has invaluable tourism resources, Romania lags far behind its European competitors in terms of attracting foreign tourists. The poor infrastructure and the lack of a clear tourism strategy make it more difficult for Romania to compete with more attractive destinations. Romania's tourism policy requires effective strategic management, a long-term integration of research and the intensification of real collaboration between the tourism industry and the Government, in order to maximize the economic potential of the tourism industry. It is about creating a political framework, an efficient infrastructure, attractive facilities for investors, consumer protection, etc., supporting tourism development with tools capable of ensuring its competitiveness in the global economy.